0732 College Student Sleep: Does it Change Over the Semester?. (27th April 2018) - Carter, P; Berkley, A
Abstract: Introduction: College students are notoriously bad sleepers. A number of factors contribute to their poor sleep ranging from new found freedoms to stress and anxiety associated with academic demands. Similarly, a number of negative consequences have been linked to poor sleep in this population ranging from academic performance decline to depressive symptoms and suicidal ideation. Interventions have been designed and implemented with the aim of improving student understanding of the importance of good sleep for success in college. This presentation will report on findings gathered over the course of a semester in two consecutive years (2015 & 2016) from students who were participating in a 15-week course focused on sleep. Methods: Undergraduate students enrolled in the UGS 303 Sleep: Are we Getting Enough? Course in the Fall 2015 and 2016 semesters were invited to participate in a longitudinal study of their sleep over the period. Data was collected on-line through RedCap and they were sent daily reminders to complete their sleep diary and up to 5 automatic reminders to complete baseline and end-of-study surveys. In addition to sleep diary data, the participants completed the PSQI, MCTQ, PSS questionnaires and provided demographic data. Data analysis is ongoing: Descriptive and relational results will be presented. Results: 191 undergraduate students participated in this study. Participants ranged in age from 18–30 years old, 60% were female, 13% were Hispanic/Latino, and 67% reported being in excellent to very good general health. Students reported average sleep latency of 18 minutes (SD=12 min) and sleep duration of 411 min (SD=60 min). Stress levels were mild to moderate. Conclusion: Students reported that over the course of the semester they not only learned the importance of sleep for their health, but also learned ways to improve their sleep quality. Final evaluations supported that students found they were empowered to make a positive change to their sleep even in the stressful context of college. Support (If Any): None.